Zika virus infection induces RNAi-mediated antiviral immunity in human neural progenitors and brain organoids - Xu, Yan-Peng; Qiu, Yang; Zhang, Boya; Chen, Guilai; Chen, Qi; Wang, Miao; Mo, Fan; Xu, Jiuyue; Wu, Jin; Zhang, Rong-Rong; Cheng, Meng-Li; Zhang, Na-Na; et al. (Cell research, 2019)
The re-emergence of Zika virus (ZIKV) in the Western Hemisphere has resulted in global public health crisis since 2015. ZIKV preferentially infects and targets human neural progenitor cells (hNPCs) and causes fetal microcephaly upon maternal infection. hNPCs not only play critical roles during fetal brain development, but also persist in adult brain throughout life. Yet the mechanism of innate antiviral immunity in hNPCs remains largely unknown. Here, we show that ZIKV infection triggers the abundant production of virus-derived small interfering RNAs in hNPCs, but not in the more differentiated progenies or somatic cells. Ablation of key RNAi machinery components significantly enhances ZIKV replication in hNPCs. Furthermore, enoxacin, a broad-spectrum antibiotic that is known as an RNAi enhancer, exerts potent anti-ZIKV activity in hNPCs and other RNAi-competent cells. Strikingly, enoxacin treatment completely prevents ZIKV infection and circumvents ZIKV-induced microcephalic phenotypes in brain organoid models that recapitulate human fetal brain development. Our findings highlight the physiological importance of RNAi-mediated antiviral immunity during the early stage of human brain development, uncovering a novel strategy to combat human congenital viral infections through enhancing RNAi.